2005
DOI: 10.1002/bit.20705
|View full text |Cite
|
Sign up to set email alerts
|

High yield production of a mutant Nippostrongylus brasiliensis acetylcholinesterase in Pichia pastoris and its purification

Abstract: The mutant M301A of the acetylcholinesterase B from Nippostrongylus brasiliensis (NbAChE) was produced in a high-cell-density fermentation of a recombinant methylotrophic yeast Pichia pastoris. Dissolved oxygen (DO) spikes were used as an indicator for feeding the carbon source. Wet cell weight (WCW) reached after 8 days a maximum value of 316 g/L and the OD600 at this time was 280. The acetylcholinesterase activity increased up to 6,600 U/mL corresponding to an expression rate of 2 g of NbAChE per liter super… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…However, the enzyme yield (146 mg.L −1 ) was lower than that of some fungal lipases in P.pastoris such as Yarrowia lipolytica (0.63 g.L −1 ) [34] and Mutant Nippostrogglus brasiliensis Acetylcholinestrease (2 g.L −1 ) [35] . Because the inducible P. pastoris expression system is able lead to production of heterologous proteins intracellularly and extracellularly up to 3 g.L −1 and 12 g.L −1 , respectively [36] – [37] , therefore, future research will be needed to enhance the opPPL yield.…”
Section: Discussionmentioning
confidence: 79%
“…However, the enzyme yield (146 mg.L −1 ) was lower than that of some fungal lipases in P.pastoris such as Yarrowia lipolytica (0.63 g.L −1 ) [34] and Mutant Nippostrogglus brasiliensis Acetylcholinestrease (2 g.L −1 ) [35] . Because the inducible P. pastoris expression system is able lead to production of heterologous proteins intracellularly and extracellularly up to 3 g.L −1 and 12 g.L −1 , respectively [36] – [37] , therefore, future research will be needed to enhance the opPPL yield.…”
Section: Discussionmentioning
confidence: 79%
“…pastoris has been widely used as a powerful eukaryotic expression system to secrete high levels of heterologous proteins under the control of AOX1 promoter induced by methanol. AChEs from different sources have been successfully produced in the P. pastoris expression system, such as from Drosophila melanogaster (Xu et al 2007), Locusta migratoria manilensis (Zhou and Xia 2011), cat flea Ctenocephalides felis (Ilg et al 2010), nematode Nippostrongylus brasiliensis (Richter et al 2006), bovine (Mendelson et al 1998) and human (Ma et al 2006). In this study, we demonstrated that rAChE from P. xylostella was first functionally expressed in P. pastoris.…”
Section: Discussionmentioning
confidence: 79%
“…It was sensitive to inhibition by methamidophos and pirimicarb, the calculated 50% inhibitory concentration (IC 50 ) values of the two pesticides were 0.357 and 0.888 mg L -1 , respectively, and the IC 70 values were 0.521 and 0.839 mg L -1 , respectively. The results suggested that it has a potential application in the detection of pesticide residues.Because this enzyme is the primary target of organophosphate (OP) and carbamate (CA) insecticides and involves in insecticide resistance known as target-site insensitivity (Soderlund and insect AChE has been extensively used in development or in vitro selection of new AChE-targeting insecticides, biological detection of pesticide residues, and in pharmacological and toxicological fields (Pang 2006;Richter et al 2006;Ilg et al 2010;Lang et al 2010;Pang et al 2010;Lu et al 2012).Since the first insect AChE gene (ace) was sequenced from Drosophila melanogaster in 1986 (Hall and Spierer 1986), the cDNAs encoding AChEs have been cloned from more than 43 insect and acarus species (Shang et al…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…C.rugosa Lip4 lipase [24] and Mutant Nippostrogglus brasiliensis Acetylcholinesterase [25] were expressed with a production level of 0.1 and 2 g/l respectively.…”
Section: Resultsmentioning
confidence: 99%